Reasons why insured consumers co-pay for medicines at retail pharmacies in Pretoria, South Africa - Ntobeko M. Mpanza; Hazel Bradley; Richard Laing (AOSIS, 2019)
Background: Costly prescription medicines with existing cheaper alternatives tend to be purchased by medically insured consumers of healthcare. In South Africa medical scheme members pay higher out-of-pocket payments for medicines than those without insurance. Aim: This study explored reasons for co-payments among insured Pretoria medical scheme members purchasing prescription medicines at private retail pharmacies, despite being insured and protected against such payments. Setting: The study took place in retail pharmacies in Pretoria, Gauteng Province, South Africa. Methods: An exploratory qualitative study was performed. Semi-structured interviews were conducted among purposefully sampled medical scheme members (12) and nine key informants (six pharmacists and three regulators - one for the pharmaceutical industry, one for medical schemes and one for pharmacists). Three pharmacies (two corporate and one independent) each were identified from high and low socio-economic areas. Scheme members were interviewed immediately after having made a co-payment (eight) or no co-payment (four) from the selected pharmacies. Interviews were recorded, coded and organised into themes. Results: Co-payments were deemed confusing, unpredictable and inconsistent between and within pharmacies. Members blamed schemes for causing co-payments. Six sampled pharmacies rarely stocked the lowest-priced medicines; instead, they dispensed medicines from manufacturers with whom they had a relationship. Corporate pharmacies were favoured compared to independents and brand loyalty superseded cost considerations. Medical scheme members did not understand how medical schemes' function. Conclusion: Unavailability of lowest-priced medicines at pharmacies contributes to co-payments. Consumer education about generics and expedited implementation of National Health Insurance could significantly reduce co-payments.